Answer:
(x+1) (x-1) (x+2) (x-2)
Step-by-step explanation:
<u>Let u = x^2</u>
= u^2 - 5u + 4
<u>(Factor u^2 - 5u + 4)</u>
= (u-1) (u-4)
<u>Substitute back u = x^2</u>
= (x^2 -1 ) (x^2 - 4)
<u>Factor x^2 - 1 and x^2 -4</u>
= (x+1) (x-1) (x+2) (x-2)
Hope this helped... :)
If you need to see the work for yourself, copy/paste this link
https://www.symbolab.com/solver/factor-calculator/factor%20x%5E%7B4%7D%20%E2%88%92%205x%5E%7B2%7D%20%2B%204%20
Answer:
A. 99.87%
Step-by-step explanation:
i don't explain things good
Answer:
27 is the answer to this equation
Step-by-step explanation:
6 times 6 equals 36
3times 3 equals 9
36
-9
27
Definitely Graph C.
The dots are aligned correctly to the line better than the other graphs.
Answer:
-5, -8, -11
Step-by-step explanation:
it every -3